Impact of Station Relocation on Observed Surface Wind Measurement Data and Its Application Effectiveness - Zhang Yongshan; Zhao Xiaodong; Yuan Chunhong; Song Lili (应用气象学报)
Surface wind speed time series from national meteorological stations are frequently utilized in studies of wind climate change analysis, wind energy resource assessment, and engineering considerations for wind resistance. Every year, dozens of weather stations are relocated in China, resulting in inhomogeneous time series data for surface wind speeds at these stations. Based on wind speed data and station history information of 2311 national meteorological stations during 2012-2023 (of which 926 stations have relocated records), the impact of station relocation on statistical values of wind speed, the causes of wind speed variation trends, and related engineering application parameters are analyzed. The results indicate that after the relocation of the stations, there is a significant increase in annual wind speed, accompanied by a noticeable decrease in the frequency of calm winds. Additionally, there are significant changes in the dominant wind direction at most stations across China. The situation of 926 stations after the relocation is as follows: The annual mean wind speed increases by 0.58-0.77 m·s-1, with an average of 0.69 m·s-1, and the wind speed at above 73% stations increases by over 20%; the annual maximum wind speed increases by 3.14-5.60 m·s-1, with an average of 4.21 m·s-1, the wind speed at above 70% stations increases by more than 20%; the annual extreme wind speed increases by 2.05-6.16 m·s-1, with an average of 4.17 m·s-1, and the wind speed increases in over 70% of stations; calm wind frequency decreases at about 75% of the stations; the dominant wind direction alters in about 76% of the stations according to 16 wind directions; and the annual mean wind speed has increased by 0.51 m·s-1 every 10 years, but the wind speed variation trends of the most nearest non-relocated stations at the same time are almost stationary. The increase in wind speed is primarily attributed to the rise in altitude following the station's relocation. These conclusions indicate that the primary cause of the overall increase in surface wind speed in China over the past decade, in the context of ongoing climate warming, is the relocation of weather stations. Further analysis results indicate that there are significant impact on the design of the maximum wind speed for the return period of engineering wind resistance concerns, which increases the cost of engineering and construction design, and analysis results of the local atmospheric diffusion capacity and direction may be altered by use of inhomogeneous wind speed of relocated stations. Therefore, when utilizing surface wind speed data for wind-related research and applications, it is essential to consider the historical information of the station. Additionally, any inhomogeneous data should be identified and processed appropriately.